2020
DOI: 10.1002/mnfr.202000854
|View full text |Cite
|
Sign up to set email alerts
|

The Garlic Compound Z‐Ajoene, S‐Thiolates COX2 and STAT3 and Dampens the Inflammatory Response in RAW264.7 Macrophages

Abstract: ScopeGarlic (Allium sativum) has been used for centuries as a prophylactic and therapeutic medicinal agent to control inflammation‐associated pathologies. To investigate the underlying mechanisms, an in vitro inflammatory model is established using RAW264.7 murine macrophages exposed to low‐doses of lipopolysaccharide (LPS) in the presence of garlic compounds allicin and Z‐ajoene (ZA), mimicking regular garlic consumption.Methods and ResultsBoth allicin and Z‐ajoene dampen both transcript and protein expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 83 publications
(140 reference statements)
0
15
0
Order By: Relevance
“…In addition to allicin, its secondary metabolite Z -ajoene has also been found to have anti-inflammatory effects. Z -ajoene has been found to inhibit the pro-inflammatory cytokine (including IL-1 β, IL-12 and IL-6 β), and up regulate the anti-inflammatory cytokine (IL = 10) ( Hitchcock et al, 2021 ). Moreover, it is reported that Z -ajoene or its analogue dansyl-ajoene was found to decrease phosphorylation and nuclear translocation of STAT3, and to covalently modify the protein by S -thiolation at Cys108, Cys367, and Cys687 ( Hitchcock et al, 2021 ).…”
Section: Allicinmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to allicin, its secondary metabolite Z -ajoene has also been found to have anti-inflammatory effects. Z -ajoene has been found to inhibit the pro-inflammatory cytokine (including IL-1 β, IL-12 and IL-6 β), and up regulate the anti-inflammatory cytokine (IL = 10) ( Hitchcock et al, 2021 ). Moreover, it is reported that Z -ajoene or its analogue dansyl-ajoene was found to decrease phosphorylation and nuclear translocation of STAT3, and to covalently modify the protein by S -thiolation at Cys108, Cys367, and Cys687 ( Hitchcock et al, 2021 ).…”
Section: Allicinmentioning
confidence: 99%
“…Z -ajoene has been found to inhibit the pro-inflammatory cytokine (including IL-1 β, IL-12 and IL-6 β), and up regulate the anti-inflammatory cytokine (IL = 10) ( Hitchcock et al, 2021 ). Moreover, it is reported that Z -ajoene or its analogue dansyl-ajoene was found to decrease phosphorylation and nuclear translocation of STAT3, and to covalently modify the protein by S -thiolation at Cys108, Cys367, and Cys687 ( Hitchcock et al, 2021 ). In the same study, Z -Ajoene was also found to inhibit the activity of cyclooxygenase 2 (COX2) in a dose-dependently and non-competitively manner, which may be attributed to the S -thiolation at Cys9 and Cys299 ( Hitchcock et al, 2021 ).…”
Section: Allicinmentioning
confidence: 99%
See 1 more Smart Citation
“…LC−MS Analysis 1 for target peptide list generation and LC−MS Analysis 2 via multiple reaction monitoring (MRM) based validation were performed according to the method previously published by Hitchcock et al 27 Statistics. All analyses were performed using GraphPad Prism v5 software (GraphPad Software, La Jolla, CA).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…AGE also regulates the inflammatory process by inducing AMPK activation and down-regulating the Toll-like receptor (TLR) signaling pathway ( Miki et al, 2017 ). Z-Ajone reduces the phosphorylation and nuclear translocation of STAT3, inhibits the activity of Cyclooxygenase-2 (COX2) ( Hitchcock et al, 2021 ), and carries out S-sulfhydrylation of cysteine sulfhydryl groups in two inflammatory proteins, thus producing downstream anti-inflammatory effects.…”
Section: The Pharmacological Activity Of Garlicmentioning
confidence: 99%